A guide to wild food foraging : proper techniques for finding and preparing nature's flavorful edibles - Squire, David, 1938- (IMM Lifestyle Books, an imprint of Fox Chapel Publishing, 2023)
The benefits of foraging for food are far and wide. Whether you're looking for ways to become more self-sufficient, save money, or develop healthier habits, A Guide to Wild Food Foraging will help! Dandelion salad, delicious wild mushrooms, fruits, herbs, and berries--you'll be surprised at what is growing in nearby fields, woods, and shores. Healthy, fresh, and free ingredients can be found in your own backyard, bringing you back to nature and our traditional roots. This book is a compact and comprehensive directory of more than 100 profiles of wild plants, herbs, fruits, nuts, mushrooms, truffles, and other edible fungi, seaweeds, and shellfish. Each profile provides tips on identification, seasonality, location, and what and when to harvest, while the mushroom section includes pictures of poisonous look-alikes to avoid. It also includes how to safely harvest your foraged treasures while being mindful of maintaining the habitat, how to prepare your bounty, and how to incorporate them into delicious recipes. Useful information is included for foraging beginners, such as the foraging code, tips for plant conservation, and questions of legality. With this book, you can add flavor to any meal for free!